ANALISIS SWOT PADA UKM MINUMAN SARI BUAH KUNYIT ASAM DI DESA PALAAN KECAMATAN NGAJUM KABUPATEN MALANG - Wibawati, Diva Aulia Putri; Al Ahdi, Muhammad Hifzhul; Izzah, Nurul; Cahyani, Winda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research was conducted based on the lack of an appropriate marketing strategy for “Fanbi Risky” fruit juice drink company, causing these companies to be underdeveloped. Therefore, it takes the right strategies to develop